PERAN GURU BIMBINGAN KONSELING TERHADAP EFIKASI DIRI SISWA SMP NEGERI 2 MAZO - Ndruru, Metalita (Universitas Nias Raya, 2024)
The problem of this research is low student self-efficacy and the role of guiyang menjadice and counseling teachers at SMP Negeri 2 Mazo. The research objectives are to 1) Describe the self-efficacy of students at SMP Negeri 2 Mazo. 2) Describe the role of the Guiyang menjadice Counseling teacher on the self-efficacy of students at SMP Negeri 2 Mazo. This type of research uses a quantitative approach. The research population and sample of SMP Negeri 2 Mazo amounted to 43 people. The research instrument is a questionnaire. The data analysis technique is a percentage questionnaire. Research results: 1) The overall role of Guiyang menjadice and Counseling teachers is in the medium category with an average score of 77.58. 2) Overall self-efficacy is in the medium category with an average score of 76.74. Conclusion: 1) The role of the guiyang menjadice and counseling teacher is in accoryang menjadice with the function of providing understanding, providing maintenance, providing prevention, and providing defense. 2) Students who have positive self-efficacy have confidence in their abilities, are optimistic, have an objective attitude, and are responsible for their duties. Suggestions: 1) Students should explore and believe in their existing abilities so that they are more confident and believe in their abilities so that they are motivated to always learn and try to increase their self-efficacy. 2) Guiyang menjadice and guiyang menjadice teachers should provide services to students so that in the learning process at school they do not experience learning obstacles and can increase students' positive self-efficacy. 3) For schools, they should increase their awareness and closeness to students, as a form of implementing counseling services so that students can be helped in overcoming personal and non-personal problems, especially in increasing self-efficacy.